2014
DOI: 10.1007/s12562-014-0797-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilization patterns of estuarine and marine habitats by the halfbeak Zenarchopterus dunckeri at Iriomote Island, southern Japan, evaluated from otolith microchemistry

Abstract: Estuarine and marine habitat use patterns in the halfbeak Zenarchopterus dunckeri were examined at Iriomote Island, southern Japan, by analyzing otolith Li/Ca and Sr/Ca ratios. The ranges of both Li/Ca and Sr/Ca ratios in juvenile Z. dunckeri from the maximum (30 psu) to minimum (0.5 psu) salinity levels of brackish water estimated from rearing experiments, were compared with those of wild individuals collected from upstream and downstream stations in the Urauchi River estuary. The majority of wildcaught indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Gene flow analysis suggested that the differentiations are due to limited contemporary gene flow (Figure ). This is supported by otolith microchemistry/stable isotopic analyses, which suggested that these species are estuarine residents but not active marine migrants (Kanai et al, ; Shirai et al, ). Although the two species are sympatric mangrove residents, they had different population structure; population differentiations in F. amboinensis were observed between Okinawa Island and the other sites, whereas each population was genetically differentiated in Z. dunckeri (Figure ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Gene flow analysis suggested that the differentiations are due to limited contemporary gene flow (Figure ). This is supported by otolith microchemistry/stable isotopic analyses, which suggested that these species are estuarine residents but not active marine migrants (Kanai et al, ; Shirai et al, ). Although the two species are sympatric mangrove residents, they had different population structure; population differentiations in F. amboinensis were observed between Okinawa Island and the other sites, whereas each population was genetically differentiated in Z. dunckeri (Figure ).…”
Section: Discussionmentioning
confidence: 83%
“…However, genomic information has not been fully exploited in the conservation of mangrove fishes, as most are nonmodel organisms with ensuing difficulty of applying molecular tools. We focused on three fish species from mangrove estuaries on the Ryukyu Islands, southern Japan (Figure 1 (Kanai et al, 2014;Shirai et al, 2018). Lutjanus fulvus, however, is a marine migrant, utilizing mangrove estuaries as nurseries and then migrating to coral reefs as they age , as commonly seen in snappers (Aburto-Oropeza, Dominguez-Guerrero, Cota-Nieto, & Plomozo-Lugo, 2009;Beck et al, 2001).…”
Section: China Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bradbury et al (2008) has reported values ~2.3 mmol/mol for Osmerus mordax (Mitchill, 1814) while Smith, Kwak (2014) reported values of ~3 mmol/mol for Gobiomorus dormitor Lacepède, 1800. However, euryhaline species were associated with significantly higher values of reference, as Mugil cephalus Linnaeus, 1758 (Sr:Ca=3.3 mmol/mol) (Fowler et al, 2016), Genidens barbus (Lacepède, 1803) (Sr:Ca=3.75 mmol/mol) (Avigliano et al, 2017b) and Zenarchopterus dunckeri Mohr, 1926 (Sr:Ca=4.2 mmol/ mol for freshwater-brackish) (Kanai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies that related salinity with the levels of Sr:Ca of otolith (Avigliano, and Volpedo, 2013a;Kanai et al, 2014;Secor et al, 1995;Shrimpton et al, 2014). For example, Kanai et al (2014) experimentally estimated the relationship between Sr:Ca of otolith and salinity for Zenarchopterus dunckeri and have subsequently used this function to study displacements of wild individuals. Secor et al (1995) performed similar approximations on the striped bass, Morone suxntilis, through laboratory tests and later making inferences about wild specimens.…”
Section: Accepted Manuscriptmentioning
confidence: 99%